2006
DOI: 10.1002/per.590
|View full text |Cite
|
Sign up to set email alerts
|

Congruence between social values and implicit motives: effects on life satisfaction across three cultures

Abstract: This study examines the relationship between implicit motives for intimacy‐affiliation and power, explicit value orientations, and life satisfaction. The Satisfaction With Life Scale, the Schwartz Value Survey, and a bias‐free TAT‐type picture‐story‐test were administered to 319 adult participants in Cameroon, Costa Rica, and Germany. The stories were coded for motive imagery reflecting needs for intimacy‐affiliation and power. Based on motives associated with the domain intimacy‐affiliation, the results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 56 publications
9
62
0
1
Order By: Relevance
“…Kehr (2004) assessed the motive congruence among managers and found a positive relation of motive congruence and emotional wellbeing. Cross-cultural studies suggested that the beneficial effects of motive-congruence and the negative effects of motive-incongruence effects are universal (Hofer and Chasiotis 2003;Hofer et al 2006). There are two explanations accounting for the negative effects of motive incongruence.…”
Section: Implicit and Explicit Affiliation Motive Congruence And Implmentioning
confidence: 99%
See 1 more Smart Citation
“…Kehr (2004) assessed the motive congruence among managers and found a positive relation of motive congruence and emotional wellbeing. Cross-cultural studies suggested that the beneficial effects of motive-congruence and the negative effects of motive-incongruence effects are universal (Hofer and Chasiotis 2003;Hofer et al 2006). There are two explanations accounting for the negative effects of motive incongruence.…”
Section: Implicit and Explicit Affiliation Motive Congruence And Implmentioning
confidence: 99%
“…Additionally, we examined participants' life satisfaction (see also Hofer et al 2006). Life satisfaction differs from the emotional well-being in so far that the latter represents people's on-line affective evaluation of the events that occur in their lives, whereas life satisfaction represents a cognitive evaluation, a more global judgment of one's life (Diener et al 1999, p. 277).…”
Section: Studymentioning
confidence: 99%
“…In recent years, empirical evidence has grown confi rming the predicted trouble by showing that the incongruence between implicit motives and explicit motives as well as between implicit motives and goals is associated with impairment of emotional well-being (e.g. Brunstein et al, 1998;Brunstein, Schultheiss, & Maier, 1999;Brunstein, Lautenschläger, Nawroth, Pöhlmann, & Schultheiss, 1995), life satisfaction (Hofer & Chasiotis, 2003;Hofer et al, 2006) and decreased physiological well-being (Baumann et al, 2005) (for the negative effects of incongruent motives in a broader sense see also Kasser & Ryan, 1996;Ryan, et al, 1999;Sheldon & Elliot, 1999;Sheldon & Kasser, 1995).…”
Section: Motive Incongruence As a 'Hidden Stressor'mentioning
confidence: 99%
“…Many studies showed that the incongruence between the affective-based implicit motive and the cognitive-based explicit motive (Baumann, Kaschel & Kuhl, 2005;Hofer & Chasiotis, 2003;Hofer, Chasiotis, & Campos, 2006), or between the implicit motive and goals (Brunstein, Schultheiss, & Grässmann, 1995;Kehr, 2004;, have negative effects on subjective as well as physiological well-being. The negative effects are explained by suggesting that these types of incongruence produce enduring intrapersonal confl icts, which work as chronic stressors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Since McClelland et al (1989) made the distinction between an implicit and an explicit motivational system, numerous studies have used these concepts to predict a variety of outcome variables (Baumann et al 2005;Brunstein and Schmitt 2004;Hagemeyer and Neyer 2012;Hofer and Chasiotis 2003;Hofer et al 2006;Job et al 2009Job et al , 2010Kazén and Kuhl 2011;Kehr 2004;Schultheiss et al 2004;Schüler et al 2010;Wegner and Schüler 2014;Woike et al 2003). However, these studies are quite heterogeneous with regard to which implicit motive measures they employed.…”
Section: Introductionmentioning
confidence: 99%